PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X FARMASI SMK KESEHATAN PRO SKILL INDONESIA - Monica Eka Yulianda; Atma Murni; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is low of mathematics learning outcomes of class X Farmasi of SMK Kesehatan Pro Skill Indonesia are still under the score of minimum mastery criteria with a percentage of 35% on the test about Matriks. This research is a class action research. That has purpose to improve the learning proses and to increase student’s mathematic learning outcomes by applied cooperative learning with Student Team Achievement Division (STAD). Subject of this research are 34 students, consist of 5 male and 29 female student with heterogenous. This research consist of two cycles that each cycle composed of 4 stages, such as planning, implementation, observation and reflection. At every end of a cycle, math achievement test will be held. The research instrument consists of learning devices and instrument data collector. The learning devices that involve Syllabus, Lesson Plan, and Worksheet. Instrument data collector that involve the observation sheet and math achievement test. Observation sheets is analyzed by narrative descriptive analysis and math achievement test analyzed by statistic descriptive analysis. The action is successful if the learning process covenient with the lesson plan and the number of students who achieve the score of minimum mastery criteria increase in math achievement test I and II. The descriptive narative showed an improvement of learning process prior to the action on the first and second cycles. The learning procces can made the student be active, cooperatife, and responsible. Based on the data analysis, the percentage of students who achieve minimum mastery before the actionis as much as 35% and at first cycleas much as 44% and at second cycleas much as 62%. The result of the research showed that, the learning process has improved and the student’s mathematics learning outcomes also increased after applying Cooperative Learning with STAD.Key Word: Learning Outcomes, Cooperative Learning with STAD, Clasroom Action Research